Occurrence, partition, and risk of seven heavy metals in sediments, seawater, and organisms from the eastern sea area of Shandong Peninsula, Yellow Sea, China - Liu, Rui; Jiang, Weiwei; Li, Fujuan; Pan, Yulong; Wang, Chunhui; Tian, Hua (Journal of environmental management, 2021)
To obtain a systematic knowledge on occurrence, partition, and risk of seven heavy metals (Cu, Pb, Zn, Cd, Cr, Hg, and As) in multi-media of marine ecosystem, sediments, seawater, and 20 species of organisms were collected from 62 sites in the eastern sea area of Shandong Peninsula, located in Yellow Sea (China), in four seasons of 2016. The concentrations were in the low-middle level compared with values from other sea areas all over the world. The highest concentrations of most of the seven elements were detected in sediments and seawater near the coastline. LogKd (distribution coefficient of sediment/water) ranged from 3.3 to 4.7. Concentrations of heavy metals in mollusc and/or crustacea were generally higher than that in fish (especially pelagic species), and while there was no significant relationships between pollutant concentrations and trophic levels. Cd and As were the most bio-accumulative elements, and As in mollusc may pose low non-carcinogenic risk We suggest that in the studied area heavy metals are mainly sourced from terrestrial input, preferentially retained by sediments, then accumulated in mollusc, and finally entered human body through mollusc consumption. Our study sounds an alarm for stricter control of metal emissions into this sea area. [Display omitted] •Concentrations of heavy metals were in the low-middle level.•Metals were mainly sourced from terrestrial input and enriched in sediments.•Mollusc showed high bioaccumulation capacity.•Cd and As were the most bio-accumulative elements.•As in mollusc may pose low non-carcinogenic risk.